Where Eagles Fly: Ancient Mountain Defences East of Rania - Mariotti, Emanuele; Merlino, Matteo (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
In autumn 2019 the Pisa Archaeological Project on the Rania Plain (KAR, Iraq) revisited and recorded some of the defensive structures on the mountain ridges east of Rania, observed and briefly described by Wheildon Brown in 1958. This short paper summarises the new evidence.